Interpretation of Fourier Transform Infrared Spectra (FTIR): A Practical Approach in the Polymer/Plastic Thermal Decomposition - Asep Bayu Dani Nandiyanto; Risti Ragadhita; Meli Fiandini (Indonesian Journal of Science and Technology, 2023)
Fourier transform infrared (FTIR) is one of the tools to represent molecular structure based on atomic vibration. It can denote a specific property of the chemical bond and molecular structure in the material, especially when analyzing specimens relating to plastics, polymers, and organic components. The FTIR peaks and spectrum act as a fingerprint of a specific molecular structure and chemical bonding, which need a sufficient reference database to distinguish them. This paper is to address issues of the need for a reference database of FTIR. This paper exhibits step-by-step information on how to read and interpret the FTIR spectra and identify a molecule's backbone with its functional groups. Practical examples from the analysis of several plastics/polymers and the thermally decomposing plastics/polymers were included to help and guide the reader to comprehend the basic concept of FTIR spectra.